International market entry mode choices by malaysian construction firms using multinomial regression model / Che Maznah Mat Isa ... [et al.] - Mat Isa, Che Maznah; Mohd Saman, Hamidah; Mohd Nasir, Siti Rashidah; Christopher, Nigel Preece (Universiti Teknologi MARA Pulau Pinang, 2014)
International market entry strategies involve three major decisions: which market to enter (entry location), when to enter the selected location (entry timing) and how to enter (entry mode). Entry modes and factors influencing the entry mode choices have been the subjects of interest in international market strategic management research but is still lacking in the construction area. Neglecting to choose a suitable entry mode and identifying the influential factors for the choice can lead to poor performance of construction firms in their international business ventures. Thus, this paper seeks to identify the entry modes preferred by the Malaysian construction firms, whether they choose equity the (EQ) mode, non-equity (NEQ) modes or both modes (BOTH) for their international projects. This study also seeks to determine the relationship between the types of mode chosen and the influential factors for the firms’ entry mode choices. The questionnaire surveys were sent to 115 construction firms listed under CIDB Malaysia (2012) resulting in a 39.1 percent response rate. Factor analysis has grouped the highly loaded factors into three components namely, firm, market and performance specific-factors which have significantly influenced the entry mode choices by the firms. A multinomial logistic regression (MLR) model has correctly classified 71.9 percent of the firms which adopted both EQ and NEQ modes and 28.1 percent used the EQ modes. The model reveals the firm-specific factor as the strongest predictor to influence the entry mode choice with logistic coefficient, B = 2.2028. The ANOVA results show no statistically difference between the entry mode types towards the influential factors. This study contributes to the literature on international business and strategy research by linking the firmspecific factors and entry mode strategy. It posits that the firm’s organizational and management supported by its strong resource capabilities has significantly influenced the firm’s choices in adopting both the EQ and NEQ modes. Hence, the significant findings in this context imply that with the identified specific factors, the firms perceive themselves as better equipped to adopt both types of entry modes for their international projects.